HUBUNGAN TIPE KEPRIBADIAN DENGAN KEJADIAN PENINGKATAN TEKANAN DARAH DI RT. 10 KELURAHAN PANAIKANG MAKASSAR - Rosdewi (Jurnal Mitrasehat, 2018)
Increased blood pressure or hypertension is a disease which is also know as a silent killer, said to be like that because the patient does not feel the symptoms. Some factors that can influence the increased of blood pressure are stress, sex, age, race, lack of sport or activity, obesity, and personality type. This research was made for the purpose of knowing the relationship between personality type with the occurrence of blood pressure raise in RT. 10 Kelurahan Panaikang Makassar. This research uses observational analytic method with cross sectional study approach. The research was conducted at RT. 10 Kelurahan Panaikang Makassar on January to February. Sampling technique used total sampling method in which all the population sampled with a sample of 40 people. The data collecting process used questionnaires on personality type, while the incidence of increased blood pressure using a sphygmomanometer and stethoscope. The result of this research was based on the Continuity Correction statistics test by value p = 0,001 and α = 0,05 means the value of p < α so that it can be concluded there is a relationship of personality types with increased incidence of blood pressure at RT 10 Kelurahan Panaikang Makassar. Someone who has the A type personality will have more risk to encounter blood pressure increase compared to someone with B type personality.